2017
DOI: 10.3389/fmicb.2017.00196
|View full text |Cite
|
Sign up to set email alerts
|

Variable Colonization after Reciprocal Fecal Microbiota Transfer between Mice with Low and High Richness Microbiota

Abstract: Several associations have been made between characteristics of the resident gut microbiota and human health and disease susceptibility. Animal models provide the means to test these correlations prospectively and evaluate causality. Experimental fecal microbiota transfer (FMT), or the intentional transplantation of gut microbes into recipient mice depleted of their autochthonous microbes with antibiotics, is a commonly used method of testing these relationships. The true completeness of microbial transfer thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 43 publications
(53 reference statements)
6
65
1
Order By: Relevance
“…Following FMT in obese individuals, Li et al identified that the dominance and resilience of transplanted species such as Roseburia hominis , Ruminococcus lactaris , and Akkermansia muciniphila were not consistently observed across individuals (53). In mice, variable colonization that can lead to functionally diverse microbiota communities has been observed in germ-free mice colonized by human microbiota (54, 55) and antibiotic-treated mice colonized by different mouse communities (56). Together, the baseline microbial community of FMT recipients and the stochastic nature of the microbial input that colonizes the recipient likely impact the ability of a microbial community to produce certain functions.…”
Section: Discussionmentioning
confidence: 99%
“…Following FMT in obese individuals, Li et al identified that the dominance and resilience of transplanted species such as Roseburia hominis , Ruminococcus lactaris , and Akkermansia muciniphila were not consistently observed across individuals (53). In mice, variable colonization that can lead to functionally diverse microbiota communities has been observed in germ-free mice colonized by human microbiota (54, 55) and antibiotic-treated mice colonized by different mouse communities (56). Together, the baseline microbial community of FMT recipients and the stochastic nature of the microbial input that colonizes the recipient likely impact the ability of a microbial community to produce certain functions.…”
Section: Discussionmentioning
confidence: 99%
“…; Ericsson et al . ). Water bottles were monitored to confirm consumption and mice were monitored on a daily basis for signs of dehydration.…”
Section: Methodsmentioning
confidence: 97%
“…Prior to fresh and frozen FMT, the recipient mice were provided ampicillin (1 g l À1 ; Wako Pure Chemical Co. Ltd., Osaka, Japan), neomycin (1 g l À1 ; Wako Chemical Co. Ltd), metronidazole (1 g l À1 ; Wako Chemical Co. Ltd) and vancomycin (500 mg l À1 ; Wako Chemical Co. Ltd) in the drinking water for five consecutive days following the previous study (Rakoff-Nahoum et al 2004;Ericsson et al 2017). Water bottles were monitored to confirm consumption and mice were monitored on a daily basis for signs of dehydration.…”
Section: Comparative Efficacy Between Fresh and Frozen Fmt Using A Mumentioning
confidence: 99%
“…In a study by Zhou et al, NSG and C57BL6/J mice whose native microbiota were depleted by antibiotics followed by FMT had no significant differences in diversity but did observe significant differences in which species colonized[39]. A study done by Ericsson et al showed that it is easier to transfer high diversity fecal donor samples into low diversity recipients, which could help to explain the success of engraftment and stability in our model[30]. Many questions remain as to the best antibiotic preconditioning regimen, the timing of fecal transplants, the total number of fecal transplants, the route of administration (oral versus rectal), the use of antacids, and preconditioning with osmotic laxatives such as polyethylene glycol, diet, and housing.…”
Section: Discussionmentioning
confidence: 94%
“…Many different methods and antibiotic regimens have been used for preconditioning of mice prior to fecal transplantation[2830]. Different combinations and durations of antibiotic treatments may increase the efficiency of the fecal transplant into the host[29].…”
Section: Discussionmentioning
confidence: 99%